Management of High Myopic Anisometropic Amblyopia: Case Study - Alkenani, Zahra'a Mehdi; Gateh, Hussain Mohammed (Journal of Science in Medicine and Life, 2024)
Anisometropic Amblyopic Myopia, characterized by significant refractive differences between the eyes, presents a challenging condition associated with vision impairment. This case study presented a 23-year-old female with Anisometropic Amblyopic Myopia, who were detailed her comprehensive nine-month management plan. The interventions included Spectacle Vision Dispensing (SVD) and Vision Therapy, combined with Spectacle Vision Correction Lenses (SVCLs) and occluder glasses. Low-dose atropine treatment was also integrated to slow myopia progression. Several parameter, including visual acuity, refraction, prescribed glasses, contact lenses, occluder glasses, keratometry, contrast sensitivity, stereo acuity, axial length, and intraocular pressure were assessed. The treatment regimen offered substantial improvements in visual acuity, contrast sensitivity, and stereo acuity, along with changes in refractive status and other ophthalmic parameters. This case highlights the potential for successful management of Anisometropic Amblyopic Myopia and high myopia through a multifaceted approach, offering valuable insights for evidence-based strategies in reducing high myopia prevalence and associated vision impairment.